CURRÍCULOS EM REDES E MOVIMENTOS DE OCUPAÇÕES NOS COTIDIANOS DO ENSINO MÉDIO: OU SOBRE JUVENTUDES E RESISTÊNCIAS - Santos, Geraldo Ferreira dos (2020)
The research was an attempt to present how the movement of occupation of a school building by high school students from the state network in Espírito Santo provoked implications in the curricular discussions. The young people's speeches called for everyon